A wiki as a common framework for promoting autonomous learning among university students. (1st January 2012) - Viciana-Abad, Raquel; Muñoz-Expósito, José Enrique; Pérez-Lorenzo, José Manuel; García-Galán, Sebastián]; Parra-Rodríguez, Fernando
The process of adapting methodologically to European Credit Transfer System suffers from a lack in practical evaluations within the engineering field. One of the main competencies within the studies of telematics engineering is the development of skills related to behaving as technical consultants. This competency has been traditionally developed via publishing additional material through learning management systems; however, the approach followed within this study has promoted its development through the creation of practical guides within a wiki. The evaluation of this activity with students of different courses is presented herein, providing certain guidelines about its use as a support system for autonomous learning.